PUBLIC SPHERE AND CIVIL SOCIETY: HABERMASIAN PERSPECTIVE - Kemi Anthony Emina (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
This work endeavours to examine the notion of public sphere as a preamble to the idea of public discourse and the inherent role of public deliberations within democratic societies. It also intends to probe as to how the need of civil society emerged within public sphere. Or, what can be the reasons that have warranted the shift of civil society from private to public and the kind of wide-ranging implications in such a shift? On the outset, this work will seek to understand the notion of public sphere (mode of Democracy) as originally conceived within socio-political conditions which influenced the processes of public opinion formation. Such an understanding of public sphere will be helpful to develop the changing notion of public sphere and civil society which is not merely limited to neo-liberal tradition. Consequently, this work also intends to analyze certain other relevant concepts such as rationality, radical form of democratic attitude, autonomy, freedom, human rights etc where public sphere has become an act of agent as discursive discourse and are related to the idea of civil society through the history of ideas in the philosophical writings of Jurgen Habermas.